HUBUNGAN STATUS GIZI DENGAN PERKEMBANGAN ANAK USIA 3 – 5 TAHUN DI KELURAHAN LEMAHIRENG KECAMATAN PEDAN KABUPATEN KLATEN - Wiwin Rohmawati; Lilik hartati (Stikes Muhammadiyah Klaten, 2019)
The age of toddlers is a period of child development, so it is necessary to pay attention to their nutritional needs. Based on reports from 35 districts / cities in Central Java Province, the number of cases of malnutrition with an indicator of body weight for height in Central Java in 2015 was 922 cases. Nutritional imbalances in children greatly affect the child's development. The purpose of this study was to determine the relationship between nutritional status and development of children aged 3-5 years in Lemahireng Village, Pedan District, Klaten Regency in 2018. This research method using correlational analytic survey method with cross sectional approach. The population of this study were all children under five in Lemahireng Village, amounting to 106 children. The sample in this study was 34 children. The sampling technique used purposive sampling. Data analysis used the Spearman Rank (Rho) correlation test. The results showed that the nutritional status with the development of children aged 3 - 5 years in Lemahireng Village was p value = 0.001 (p <0.05), so that Ho was rejected. The conclusion in this study is that there is a relationship between nutritional status and the development of children aged 3-5 years in Lemahireng Village, Pedan District, Klaten Regency. It is suggested that parents can provide stimulation from an early age to children and further increase their knowledge about child development by consulting health workers and providing balanced nutrition because it is very important for children's development.